Unipolar versus bipolar hemiarthroplasty for displaced femoral neck fractures: A pooled analysis of 30, 250 participants data. Issue 10 (October 2019) - Imam, Mohamed A.; Shehata, Mohamed; Abdallah, Ahmed R.; Ahmed, Hussien; Kader, Nardeen; Ernstbrunner, Lukas; Narvani, Ali A.; Kambouroglou, Gregoris; Mcnamara, Iain; Sallam, Asser A.
Highlights: Bipolar hemiarthroplasty offers greater range of motion and less acetabular erosion than unipolar hemiarthroplasty. The operative time was longer during bipolar hemiarthroplasty compared to unipolar hemiarthroplasty. No significant difference in hip function using Harris hip score, mortality, surgical, and medical outcomes is evident. Abstract: Purpose: To assess the clinical outcomes of unipolar versus bipolar hemiarthroplasty for displaced intracapsular femoral neck fractures in older patients and to report whether bipolar implants yield better long-term functional results. Methods: We searched PubMed, Scopus, EBSCO, and Cochrane Library for relevant randomized clinical trials (RCTs) and observational studies, comparing unipolar and bipolar hemiarthroplasty. Data were extracted from eligible studies and pooled as relative risk (RR) or mean difference (MD) with corresponding 95% confidence intervals (CI) using RevMan software for Windows. Results: A total of 30 studies were included (13 RCTs and 17 observational studies). Analyses included 30, 250 patients with a mean age of 79 years and mean follow-up time of 24.6 months. The overall pooled estimates showed that bipolar was superior to unipolar hemiarthroplasty in terms of hip function, range of motion and reoperation rate, but at the expense of longer operative time. In the longer term the unipolar group had higher rates of acetabular erosion compared to the bipolar group. There was no significant difference in terms of hip pain, implant related complications, intraoperative blood loss, mortality, six-minute walk times, medical outcomes, and hospital stay and subsequently cost. Conclusions: Bipolar hemiarthroplasty is associated with better range of motion, lower rates of acetabular erosion and lower reoperation rates compared to the unipolar hemiarthroplasty but at the expense of longer operative time. Both were similar in terms of mortality, and surgical or medical outcomes. Future large studies are recommended to compare both methods regarding the quality of life.